Racial/ethnic disparities in gastric cancer: A 15‐year population‐based analysis. (3rd July 2022) - Gonzalez‐Pons, Maria; Torres‐Cintrón, Carlos R.; Soto‐Salgado, Marievelisse; Vargas‐Ramos, Yimari; Perez‐Portocarrero, Luis; Morgan, Douglas R.; Cruz‐Correa, Marcia
Abstract: Background and aims: Disparities in gastric cancer incidence and mortality have been reported among ethnic/racial groups. While gastric cancer is not common in the U.S., it is among the top 10 causes of cancer‐related death among Hispanics living in Puerto Rico (PRH). This study compared gastric cancer incidence rates during a 15‐year period (2002–2006, 2007–2011, and 2012–2016) between PRH and racial/ethnic groups in the mainland U.S., including Non‐Hispanic Whites (NHW), Non‐Hispanics Blacks (NHB), Hispanics (USH), and Non‐Hispanic Asian or Pacific Islanders (NHAPI). Methods: Primary gastric cancer cases (ICD‐O‐3 codes C16.0 to C16.9) from the Puerto Rico Central Cancer Registry and SEER diagnosed from January 1, 2002 to December 31, 2016 were included in the analysis. The Joinpoint Regression Program and standardized rate ratios were used to estimate Annual Percent Changes (APC) and differences in gastric cancer incidence among racial/ethnic groups, respectively. Results: Our analysis included 83, 369 gastric cancer cases (PRH n = 4202; NHW n = 43, 164; NHB n = 10, 414; NHAPI n = 11, 548; USH n = 14, 041). USH had the highest number of cases among individuals <50 years, whereas NHW and PRH had the highest percentage among individuals ≥50 years. PRH and USH were the only groups with increasing APCs among individuals <50 years. Conclusions: Gastric cancer continues to be a common cancer among PRH, despite the overall decrease in incidence among other racial/ethnic groups. Studies evaluating the gastric cancer risk factors among high‐risk groups are necessary to establish health policy and modify gastric cancer screening algorithms among Hispanics. Abstract : Among Hispanics, gastric tumors continue to be commonly diagnosed; only 32% of individuals diagnosed with this malignancy survive more than 5 years. An increase in gastric cancer among individuals younger than 50 years and diagnosis at regional (more advanced) stages was observed when comparing Hispanics living in Puerto Rico to other racial/ethnic groups on the U.S. mainland. Our findings underscore the importance of evaluating gastric cancer risk factors among diverse, high‐risk groups, such as Hispanics, in order to develop tailored prevention and risk stratification strategies.